The effect of preliminary training on quantitative evaluation of sonographer performance in the fetal morphology ultrasound examination. Issue 3 (August 2013) - Lam, Penny; Samson, Armie; Magotti, Robert; Benzie, Ronald
Abstract: Introduction : The aim of this study is to provide a quantitative scoring system to assess sonographer performance by reviewing images from the fetal morphology examination. Methods : Ten ultrasound images from patients at 18–22 weeks gestation were assessed and scored for quality according to predefined criteria. One hundred normal cases were randomly selected and 10 images from each case were analysed by four experienced reviewers. The preliminary training incorporated the first 25 cases and involved a training period for reviewers; the remaining 75 cases were allocated to post training. The scores acquired by each reviewer were statistically analysed using Pearson's and intra‐class correlations to determine the reproducibility of the results. Results : The preliminary training results were calculated separately and compared to the post training study. The preliminary intra‐class correlation coefficient was 0.12. In the post training study the intra‐class correlation coefficient was doubled at 0.24. The greatest correlation was observed between reviewers 1 and 4 with a coefficient of 0.71. Reviewers 3 and 4 demonstrated the lowest correlation coefficient of 0.30. Discussion : A significant increase in the intra‐class correlation coefficient indicated that training reviewers achieves more reproducible results. Suggested improvements to the study include recording fetal position, maternal BMI and assessing individual reviewer variability. An instruction manual defining each criterion might also yield better results. Conclusion : The quantitative method used in this study assessed ultrasound images by placing a numerical value on image quality. Analysis of the preliminary training period demonstrates improved reproducibility of the results. Further investigation into the criteria is necessary to refine the quantitative method.